ГИПОКСИЧЕСКИЙ ГЕПАТИТ - Г. Сторожаков; Р. С. Осканова; Л. Ю. Ильченко; С. Д. Косюра; И. Г. Фёдоров (SINAPS LLC, 2014)
Presentation of hypoxic hepatitis (НН) over the past 20 years have evolved from purely laboratory indicator to important clinical concepts, which has a great practical importance for clinicians. Unfortunately, in clinical practice НН diagnosed in connection with the non-specificity of the clinical manifestations, and lack of awareness of General practitioners about the disease. Most often, the disease is diagnosed in patients in intensive care and is associated with high mortality. In this literature review, we analyzed the available epidemiological and pathogenic data, clinical aspects, high risk factors and possible outcomes of the НН.